Deauville : création et développement urbain - Didier Hébert (In Situ)
During the nineteenth century, the success of Trouville, with its reputation founded on the novel practices of therapeutic sea bathing, gave rise to the development of seaside resorts all along France’s Channel coast. Their creation was based on speculative initiatives which followed a similar general pattern: the purchase of real estate by a private speculator and the creation of a development company charged with dividing the land into parcels and commercialising the individual building plots. This company was also responsible for the layout of the resort’s streets and for building its public seaside facilities. This process of appropriation of the Channel coast, notably on the maritime edge of Normandy’s Pays d’Auge, was particularly dynamic during the middle of the century, with the creation of Cabourg in 1854 (under the impulsion of the Paris lawyer Henri Durand), Villers-sur-Mer in 1856 (at the initiative of the architect Félix Pigeory), Houlgate in 1858 (under the direction of the architect Jacques Baumier) and Deauville the following year.